An Analysis of Figurative Language and Language Style Used in Friends Season 8 Script - Riyuda, Muhammad; Oktoviandry, Rifki (Universitas Negeri Padang, 2024)
Figurative language is a language that has non-literal meaning or other meaning. This study aims to find out the type of figurative language and the contextual meaning used in Friends season 8 script and the types of language style used in figurative language in Friends season 8 script. This study uses several theories to provide its analysis. Perrine’s theory was used to analyze the type of figurative language, Lyons’s theory was used to analyze the contextual meaning of the figurative language, and Joos’s theory was used to analyze the type of language style from the utterance of the figurative language. A qualitative method was used in this study to analyze the data. There are 54 utterances of figurative language found in Friends season 8 script. There were eight metaphors, 14 similes, eight apostrophes, 13 hyperboles, two metonymy, two irony, five personifications, and two understatements. The contextual meaning of the figurative language shows the real or hidden meaning of what the character said. Then, the language style from the 54 utterances of figurative language was one consultative style, 49 casual styles, and four intimate styles. The most dominant figurative language used in Friends’ season 8 script was simile, and the language style was casual.